2017
DOI: 10.1071/cp17028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual and combined heat and drought stress during seed filling on the oxidative metabolism and yield of chickpea (Cicer arietinum) genotypes differing in heat and drought tolerance

Abstract: Drought and heat stress are two major constraints that limit chickpea (Cicer arietinum L.) yield, particularly during seed filling. The present study aimed (i) to assess the individual and combined effects of drought and heat stress on oxidative metabolism during seed filling, and (ii) to determine any genetic variation in oxidative metabolism among genotypes differing in drought and heat tolerance and sensitivity. The plants were raised in outdoor conditions with two different times of sowing, one in November… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 78 publications
4
41
1
Order By: Relevance
“…GSH content in our experiment increased with the time as drought stress prolonged in all three varieties. Awasthi et al [68] also witnessed elevated GSH content under drought stress conditions, thus triggers adaptive responses, which is in line with our findings.…”
Section: Non-enzymatic Antioxidant Defense System Involved In Mitigatsupporting
confidence: 93%
“…GSH content in our experiment increased with the time as drought stress prolonged in all three varieties. Awasthi et al [68] also witnessed elevated GSH content under drought stress conditions, thus triggers adaptive responses, which is in line with our findings.…”
Section: Non-enzymatic Antioxidant Defense System Involved In Mitigatsupporting
confidence: 93%
“…Moreover, upon exposure to both stresses at the same time, the lentil leaves showed extensive damage to their membranes (as indicated by high EL), chlorophyll content, and photosynthetic efficiency, which might be attributed to a significant reduction in leaf water status and stomatal conductance (Awasthi et al, 2014). Damage to membranes may occur due to the direct impacts of these stresses (Guadagno et al, 2017;Horváth et al, 2012) or intense oxidative stress generated by two stresses (Johnson et al, 2014) and has been reported in chickpea (Awasthi et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, upon exposure to both stresses at the same time, the lentil leaves showed extensive damage to their membranes (as indicated by high EL), chlorophyll content, and photosynthetic efficiency, which might be attributed to a significant reduction in leaf water status and stomatal conductance (Awasthi et al, ). Damage to membranes may occur due to the direct impacts of these stresses (Guadagno et al, ; Horváth et al, ) or intense oxidative stress generated by two stresses (Johnson et al, ) and has been reported in chickpea (Awasthi et al, ). Chlorophyll loss is attributed to increased photo‐oxidation (Guo, Zhou, & Zhang, ), dehydration, inhibited synthesis, or increased degradation (Tewari & Tripathy, ), which matches the observations in chickpea (Awasthi et al, ), tomato (Nankishore & Farrell, ), and rice (Kumar, Vijayalakshmi, & Vijayalakshmi, ) exposed to both stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial losses observed in crop yields under combined stress environment have been attributed to several reasons, such as metabolic changes, reductions in the period of crop developmental stages ( Reddy et al, 2004 ). Subsequent decline in light perception, decreased phenology, and perturbation of processes involved in carbon assimilation such as transpiration, photosynthesis and respiration may contribute to fewer, malformed and smaller seeds ( Barnabás et al, 2008 ; Awasthi et al, 2014 , 2017 ), which are economically futile.…”
Section: Combined Effect Of Heat and Drought Stresses On Seed Fillingmentioning
confidence: 99%